Establishment of a neonatal resuscitation registry in the Democratic Republic of the Congo: An open cohort study - Amy Mackay; Daniel Ishoso; Eric Mafuta; Joar Eilevstjønn; Patricia Gomez; Waldemar Carlo; Melissa Bauserman; Carl Bose; Jackie K. Patterson (PLoS ONE, 2025)
Improving neonatal resuscitation practices reduces neonatal mortality. In low- and middle-income countries (LMICs), granular details about provider actions during resuscitation are largely unknown; therefore, identifying targets for improvement is difficult. The International Liaison Committee on Resuscitation (ILCOR) recognizes the importance of uniform reporting of clinical neonatal resuscitation studies and published a guideline recommending specific variables to include. We established an open cohort study for newborn resuscitation in the Democratic Republic of the Congo (DRC) as a platform for developing and evaluating novel strategies to improve newborn resuscitation. We included all in-born neonates at two health facilities in Kinshasa, DRC. We gathered data on all enrollees via delivery registry and medical record abstraction. Using the Liveborn Observation app, we directly observed care at birth for a convenience sample. We collected heart rate data when providers used NeoBeat, a battery-operated heart rate meter. From September 2022 to August 2023, we abstracted delivery registry and medical record data for 6,414 newborns and gathered observational data on the infant’s breathing status and provider actions for 3,166 (49%). Our dataset includes 85% of ILCOR’s recommended core variables applicable to this setting, and 50% of ILCOR’s applicable supplemental variables. Our registry also contains variables beyond those recommended by ILCOR that are contextually important for evaluating resuscitation care in LMICs such as duration of suctioning, pauses in positive pressure ventilation and fresh stillbirth. Our experience establishing a resuscitation registry with novel tools in the DRC serves as a model for resuscitation research in low-resource settings. Our cohort study provides important insight to inform subsequent versions of ILCOR’s guideline on uniform reporting of neonatal resuscitations studies globally.